A Design for a Trusted Community Bathymetry System. Issue 4 (3rd July 2020) - Calder, Brian R.; Dijkstra, Semme J.; Hoy, Shannon; Himschoot, Kenneth; Schofield, Andrew
Abstract: Marine Volunteered Geographic Information (informally "crowdsourced bathymetry") has raised much interest within the authoritative hydrographic community as a means to cheaply gather information to satisfy chart updating requirements. So far, however, a routine path to the official chart has been rare, mainly due to lack of calibration and other metadata that would satisfy liability concerns. As an alternative to these ideas, a data collection system is proposed which, by design, can auto-calibrate and provide other data quality guarantees, and thereby generate data that by construction should be qualified for hydrographic use. This idea is termed here Trusted Community Bathymetry (TCB). A design for such a system is outlined, and its performance demonstrated experimentally through a prototype system based on a low-cost, post-processed GNSS receiver and NMEA data logger. By comparison against NGS control and survey-grade GNSS equipment, it is shown that the TCB system achieves centimeter to decimeter-level positioning in 3D, auto-calibrates vertical offsets to the sonar transducer within a decimeter, and provides realtime uncertainty estimates for ellipsoid-referenced soundings. Additionally, in an underway field trial, the total vertical uncertainty of the soundings is shown to be within the limits required for IHO Order 1b (S.44, 5 Ed.) surveys.